Supplementary Schools and Ethnic Minority Communities A Social Positioning Perspective - Simon, Amanda (Palgrave Macmillan UK, 2018)
This book provides a unique perspective into the world of supplementary schooling, exploring both the social positioning of these schools and the ethnic minority communities they serve. The author presents a close examination of the establishment and functioning of supplementary schools which offers a fresh and novel insight into acculturation processes. Drawing on empirical data gathered from staff interviews, classroom observations and interactive recordings, this book explores the operation of supplementary schools as sites of identity construction where the community identities are preserved, defended, renegotiated and reconstructed. The various modes of construction are indicative of the acculturation experiences of ethnic minority communities and the ways in which these communities negotiate residence in one country whilst having roots in another. This book therefore offers a revealing conceptualization of supplementary schools, not merely as educational spaces, but socio-political enterprises that are situated within and respond to various historical, social and political contexts. This pioneering work will appeal to students and scholars in the fields of education, migration and identity.